2023
DOI: 10.3389/fmed.2022.1097133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prognosis of patients with endometrial cancer after hysteroscopy versus dilatation and curettage: A multicenter retrospective study

Abstract: IntroductionHysteroscopy is a useful procedure for diagnosing endometrial cancer. There is controversy regarding whether hysteroscopy affects the prognosis of endometrial cancer by prompting cancer cell into intraperitoneal dissemination. Our purpose was to confirm whether hysteroscopy could be a risk factor of the tumor stage, recurrence and survival rate of endometrial cancer.MethodsThis multicenter retrospective study included all consecutive patients who had endometrial carcinoma diagnosed preoperatively w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Similar results were also reported in two other studies [20,21]. Liu et al [10] detected 12 positive peritoneal cytology in 77 patients with endometrial cancer diagnosed with hysteroscopy had a 5-year recurrencefree survival rate and specific disease survival rate of 91.8% and 85.4% respectively. These results deserve special attention because the patients exhibited low-risk characteristics (71 patients were clinical stage I-II, 71 had no lymphovascular disease, and 44 had less than 50% of uterine wall involvement), demonstrating that hysteroscopy is not an independent risk factor for positive peritoneal cytology or worsening the prognosis of the disease.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were also reported in two other studies [20,21]. Liu et al [10] detected 12 positive peritoneal cytology in 77 patients with endometrial cancer diagnosed with hysteroscopy had a 5-year recurrencefree survival rate and specific disease survival rate of 91.8% and 85.4% respectively. These results deserve special attention because the patients exhibited low-risk characteristics (71 patients were clinical stage I-II, 71 had no lymphovascular disease, and 44 had less than 50% of uterine wall involvement), demonstrating that hysteroscopy is not an independent risk factor for positive peritoneal cytology or worsening the prognosis of the disease.…”
Section: Discussionsupporting
confidence: 86%
“…However, it does not impact the recurrence, overall survival or disease-free survival rate [8,9]. On the other hand, there are other studies where this correlation has not been observed [10,11].…”
Section: Introductionmentioning
confidence: 92%
“…Many researchers have reported positive peritoneal cytology rates, whereas others have not confirmed such changes. Hysteroscopy can improve diagnostic accuracy and, compared with D&C, did not increase the risk of intraperitoneal dissemination in 147 EC patients in a previous study 18 . Some retrospective studies have shown that hysteroscopy with morcellation is a safe diagnostic procedure for EC, even high‐risk and type II EC, and that it does not lead to increased dissemination of cancer cells, LVSI or surgical upstaging of tumors 19,20 .…”
Section: Discussionmentioning
confidence: 87%
“…Hysteroscopy can improve diagnostic accuracy and, compared with D&C, did not increase the risk of intraperitoneal dissemination in 147 EC patients in a previous study. 18 Some retrospective studies have shown that hysteroscopy with morcellation is a safe diagnostic procedure for EC, even high‐risk and type II EC, and that it does not lead to increased dissemination of cancer cells, LVSI or surgical upstaging of tumors. 19 , 20 A retrospective cohort analysis evaluated the outcome measures of 392 EC patients diagnosed by endometrial biopsy, D&C or hysteroscopy and found that hysteroscopy did not significantly affect the survival outcomes and recurrence of endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions were drawn from a retrospective multicenter study, which compared two groups of patients with endometrial cancer that did not differ by age, BMI, tumor stage, histological type, peritoneal cytology result, depth of myometrial invasion, infiltration of lymphovascular spaces, and lymph node status. There were no statistically significant differences in overall survival and recurrence-free time between patients whose diagnosis of endometrial cancer was made based on histopathological examination of material from hysteroscopic biopsy and classical uterine curettage [ 69 ].…”
Section: Hysteroscopy and Laparoscopymentioning
confidence: 99%